2017
DOI: 10.1111/1744-7917.12446
|View full text |Cite
|
Sign up to set email alerts
|

Male age and strain affect ejaculate quality in the Mexican fruit fly

Abstract: Aging in all organisms is inevitable. Male age can have profound effects on mating success and female reproduction, yet relatively little is known on the effects of male age on different components of the ejaculate. Furthermore, in mass-reared insects used for the Sterile Insect Technique, there are often behavioral differences between mass-reared and wild males, while differences in the ejaculate have been less studied. The ejaculate in insects is composed mainly of sperm and accessory gland proteins. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Further, old D. melanogaster males are defective at transferring SFPs despite a higher SFP abundance compared to young males ( Sepil et al, 2020 ). Protein concentration also increases with age in the accessory glands of old D. bipectinata ( Santhosh and Krishna, 2013 ) and Anastrepha ludens males ( Herrera-Cruz et al, 2018 ). However, in A. socius , an SFP that induces egg laying decreases in abundance as males age ( Marshall et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, old D. melanogaster males are defective at transferring SFPs despite a higher SFP abundance compared to young males ( Sepil et al, 2020 ). Protein concentration also increases with age in the accessory glands of old D. bipectinata ( Santhosh and Krishna, 2013 ) and Anastrepha ludens males ( Herrera-Cruz et al, 2018 ). However, in A. socius , an SFP that induces egg laying decreases in abundance as males age ( Marshall et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that delayed mating may reduce the quality of male sperm, and thereby reduce egg hatching. Sperm quality can decrease with male age, which can lead to decreased ability to inseminate females [ 32 , 33 ]. We found that males can mate normally at 7 d after emergence.…”
Section: Discussionmentioning
confidence: 99%
“…the cricket Allonemobius socius, Marshall et al 2009; the blue-footed booby, Kim et al 2011; the houbara bustard, Preston et al 2015) but this is not universal (for flies e.g. Santhosh & Krishna 2013, Dhole & Pfennig 2014, Herrera-Cruz et al 2018.…”
Section: Senescence Of Male Post-mating Traitsmentioning
confidence: 99%
“…Also often single measures of age-dependent changes in sperm number or morphology are not linked to fertilisation ability (for e.g. by Moller et al 2009, Gasparini et al 2014, Herrera-Cruz et al 2018. It is often implicitly assumed that age-dependent changes would result in a diminished fertilisation success; however, this is not necessarily the case as in some species like D. bipectinata and D. pseudoobscura, older males have higher reproductive success than younger males.…”
Section: Sperm and Testes Ageingmentioning
confidence: 99%